A comprehensive meta-analysis reveals the key variables and scope of seed defense priming - Talavera-Mateo, Lucia; Garcia, Alejandro; Santamaria, M. Estrella (Frontiers in Plant Science, 2023)
Background When encountered with pathogens or herbivores, the activation of plant defense results in a penalty in plant fitness. Even though plant priming has the potential of enhancing resistance without fitness cost, hurdles such as mode of application of the priming agent or even detrimental effects in plant fitness have yet to be overcome. Here, we review and propose seed defense priming as an efficient and reliable approach for pathogen protection and pest management. Methods Gathering all available experimental data to date, we evaluated the magnitude of the effect depending on plant host, antagonist class, arthropod feeding guild and type of priming agent, as well as the influence of parameter selection in measuring seed defense priming effect on plant and antagonist performance. Results Seed defense priming enhances plant resistance while hindering antagonist performance and without a penalty in plant fitness. Specifically, it has a positive effect on crops and cereals, while negatively affecting fungi, bacteria and arthropods. Plant natural compounds and biological isolates have a stronger influence in plant and antagonist performance than synthetic chemicals and volatiles. Discussion This is the first meta-analysis conducted evaluating the effect of seed defense priming against biotic stresses studying both plant and pest/pathogen performance. Here, we proved its efficacy in enhancing both, plant resistance and plant fitness, and its wide range of application. In addition, we offered insight into the selection of the most suitable priming agent and directed the focus of interest for novel research.